PRODUCTION AND CHARACTERIZATION OF CHITOSANASE ENZYME FROM STREPTOMYCES SP ISOLATED FROM BIOWASTE SOIL SAMPLES - P.VANATHI; P.PREMASUDHA; DR.R.RAJENDRAN (International Journal of Pharma and Bio Sciences, 2016)
Chitin is one of the most abundant biopolymers widely distributed in the marine and terrestrial environments. Chitosanase enzyme has received increased attention due to its wide range of biotechnological applications. In the present study, actinomycetes isolates were screened for chitosanolytic activity and on the basis of chitosan hydrolysis zone 6 isolates were selected for chitosanase production in broth media. Based on enzyme production, the most potent isolate identified as Streptomyces sp SA4 was selected for further study. The effects on media composition and various fermentation conditions for optimization of chitosanase production were studied. The maximum chitosanase production was obtained at 28°C and pH 6.0 after 72 h of incubation. Among the substrates soluable chitosan (1.5%) was the best for both the strain. Regarding carbon sources, xylose (1%) was the best; while (1%) ammonium chloride was found as the best nitrogen source. The enzyme activity was maximum pH 7 and at 40°C. The crude chitooligosaccharides was prepared with SA4 enzyme and was checked for its antibacterial activity against pathogens.